HEGEMONY OF INTERNATIONAL STANDARD EDUCATION AT PUBLIC SENIOR HIGH SCHOOL 78 JAKARTA - Sinaga, Tuntun (E-Journal of Cultural Studies, 2014)
The Act Number 20 of 2003 concerning System of National instructed that international standard education unit be opened in every regency/city in every part of Indonesia as an attempt made to anticipate the globalized era. This study was intended to understand the forms of hegemony of PBI and the factors contributing to it at Public Senior High School 78 Jakarta. In the present study, the Theory of Hegemony, the Theory of Discourse of Power/Knowledge, and the Theory of Social Practice were eclectically used with qualitative approach. The data were taken from documents, brochures, mass media, experts in education, community leaders, teachers, students, parents and the headmaster. The data were taken through interview, observation and documentary study. The data were validated through the process of triangulation which includes data reduction, data presentation, data verification, and interpretation.  The result of the study showed that (1) the hegemony of PBI took place in the forms of the standardization of education, the capitalization of education, the image of international quality, the stratification of education and (2) the factors contributing to the hegemony of PBI were the politics of national education and the discourse of globalism. Hegemony took place in the form of internationalization of eight SNP and “benchmarking” of the quality of education in OECD countries in order to anticipate globalization. It is suggested that the general middle education which reflected the philosophy of national education, Pancasila, need to be reconstructed.
Keywords: hegemony, standardization of education, globalization.